Loyalty - Avi, 1937- (Clarion Books, 2022)
When Noah Cope's Loyalist father is killed by a mob of patriot neighbors, he and his family leave their small town for Boston, Massachusetts. Wanting revenge for his father's death, Noah becomes a British spy and ordered to eavesdrop on the rebels meeting at a local tavern. But when he befriends a young Black freeman named Jolla, who opens Noah's eyes to the hypocrisy of men who demand freedom all while enslaving others, he must decide where his loyalties truly lie.